Comparison of adequacy of blood flow between proximal forearm AV fistula placed at elbow and distal forearm AV fistula placed at wrist in the early post-operative period - Prateek Kapase,; Anand S Gajakos,; Vikas R Lonikar, (Asian Journal of Medical Sciences, 2023)
Background: In patients with a failed DRCF or unsuitable for DRCF, the current recommendation is to perform a brachiocephalic fistula. Proximal forearm radiocephalic fistulas are created less frequently. Aims and Objectives: The aim of the present study was to evaluate the outcomes of proximal forearm AV fistula placed at elbow and distal forearm AV fistula placed at wrist in terms of adequacy of blood flow in the early post-operative period. Materials and Methods: The present cross-section study was conducted on patients with end-stage renal disease with proximal or distal AV fistula at wrist for a period of 2 years at radiodiagnosis department. The patients were divided into two groups, those with proximal AVF and those with distal AVF. The Doppler ultrasound findings were analyzed and compared between the two groups to identify any differences that could be associated with the success or failure of the AVF. Results: The difference in mean arterial diameter between the proximal and distal groups may indicate that the proximal fistulas have a better chance of providing adequate blood flow for dialysis. The difference in TAV between proximal and distal group may indicate difference in the location and type of fistula and the blood vessels involved in them. Conclusion: Proximal forearm AV fistula is an appealing option to brachiocephalic fistulas in failed distal forearm AV fistula and patients who cannot obtain a distal radiocephalic fistula because to their much lower initial failure rate, higher patency rate, and reduced complication rate.